Exploring the Connection between Entrepreneurship and Family Business in Indonesian Family SMEs - Kussudyarsana, K; Maimun, Muhammad Halim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Family business is an important business entity that contribute to the world economy, including Indonesia. This study explored the linkages between family business and entrepreneurship in Indonesia. Several business aspects where investigated in this study included financial and human capital, and business governance. Purposive sampling will be used as a sampling design of this research. The Samples of this research are the entrepreneurs who start the business. This research will use mixed method, combine between qualitative and quantitative research. In here, qualitative method is conducted through interview and focuses group discussion, while quantitative method with questionnaire. Some question about the activities and resources during business start up were asked to them. During the process interview, the explanations were recorded and some critical information was outlined, and rewrites in paper work.